Spectroscopic evaluation of UVI–cement mineral interactions: ettringite and hydrotalcite. (15th December 2021) - Yorkshire, Antonia S.; Stennett, Martin C.; Walkley, Brant; O'Sullivan, Sarah E.; Mottram, Lucy M.; Bailey, Daniel J.; Provis, John L.; Hyatt, Neil C.; Corkhill, Claire L.
Abstract : A U L III ‐edge X‐ray absorption spectroscopic investigation of U VI interactions with minor cement minerals, ettringite and hydrotalcite, is reported. The study is supplemented by 27 Al magic angle scattering nuclear magnetic resonance spectroscopy, X‐ray diffraction and geochemical modelling. Abstract : Portland cement based grouts used for radioactive waste immobilization contain high replacement levels of supplementary cementitious materials, including blast‐furnace slag and fly ash. The minerals formed upon hydration of these cements may have capacity for binding actinide elements present in radioactive waste. In this work, the minerals ettringite (Ca6 Al2 (SO4 )3 (OH)12 ·26H2 O) and hydrotalcite (Mg6 Al2 (OH)16 CO3 ·4H2 O) were selected to investigate the importance of minor cement hydrate phases in sequestering and immobilizing U VI from radioactive waste streams. U L III ‐edge X‐ray absorption spectroscopy (XAS) was used to probe the U VI coordination environment in contact with these minerals. For the first time, solid‐state 27 Al magic angle spinning nuclear magnetic resonance (MAS‐NMR) spectroscopy was applied to probe the Al coordination environment in these U VI ‐contacted minerals and make inferences on the U VI coordination, in conjunction with the X‐ray spectroscopy analyses. The U L III ‐edge XAS analysis of the U VI ‐contacted ettringite phases found them to be similar (>∼70%) to the uranyl oxyhydroxides present in a mixed becquerelite/metaschoepite mineral. Fitting of the EXAFS region, in combination with 27 Al NMR analysis, indicated that a disordered Ca‐ or Al‐bearing U VI secondary phase also formed. For the U VI ‐contacted hydrotalcite phases, the XAS and 27 Al NMR data were interpreted as being similar to uranyl carbonate, that was likely Mg‐containing.